THE KWLM TECHNIQUE: SUSTAINING INTERESTS AND ENHANCING MOTIVATION IN READING - Ive Emaliana (Universitas Brawijaya, 2013)
The common phenomenon among students, which becomes the persistent problem faced by many English teachers, is the attempt to sustain genuine interest in continuing to learn and use English, especially reading once the examinations are over. Teachers have to create a healthy balance between preparing students for the standardized examination and for life-long language skills. Utilizing an effective teaching technique like the KWLM can encourage students to read actively through the learning events and promote students motivation to read. This technique assists teachers to make students comprehend reading texts through charts that include column for each activity on activating students’ prior knowledge, expressing their curiosity, explaining information gotten, and extending information on the topic. As it provides an opportunity for students to expand their ideas by reading more texts, they are indirectly trained to do self-directed reading. This is justified by the students responses towards the questionnaires distributed. By utilizing the KWLM technique, the ultimate goal of language teachers to help learners become autonomous readers can be achieved. Keywords: The KWLM Technique, autonomous learner.